Peran Kepemimpinan Berjiwa Wirausaha Dalam Mewujudkan Pendidikan Islam Yang Berkualitas - Azarine Kamila Efendi; Siti Nurafida; Fariyatul Aini; Mahardika Anugrah (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2024)
Entrepreneurial leadership has a strategic role in developing quality Islamic education. This kind of leadership is characterized by innovative ability, measured risk-taking, and competitive results orientation. In the context of Islamic education, a leader with an entrepreneurial spirit is able to create a strong vision, inspire the team, and optimally utilize resources to support the achievement of holistic educational goals. Entrepreneurial leaders focus on institutional transformation, particularly through the development of relevant curricula, innovative educational technology and strengthening an inclusive learning culture. With this approach, Islamic educational institutions not only act as learning centers but also as agents of social change. In addition, this leadership approach encourages close collaboration between various stakeholders, both internal and external, to strengthen networks and support educational sustainability. The proactive and adaptive attitude of entrepreneurial leaders is able to face the challenges of globalization and changing times. By prioritizing Islamic values as a moral foundation, this leadership ensures that the innovations and developments carried out remain in line with the main objective of Islamic education, which is to produce human beings who have faith, knowledge and noble character. Therefore, the role of entrepreneurial leadership is a key element in creating an Islamic education.